Archaeological evidence for Holocene landslide activity in the Eastern Carpathian lowland. (10th September 2016) - Niculiţă, Mihai; Mărgărint, Mihai Ciprian; Santangelo, Michele
Abstract: Landslides are widespread phenomena that contribute to shape the landscape. Assessing the time sequence of landslide activity during the Holocene can help (i) better frame the present day landslide distribution in the wider context of climate change and (ii) better define landslide hazard to take adequate mitigation measures to preserve the elements at risk such as archaeological heritage and currently used structures and infrastructures. Rigorous image interpretation criteria applied to the interpretation of remote sensing images can be a valuable tool to derive information on landslide spatial and temporal distribution. However, it only allows to broadly estimate the relative age of landslides based on their morphologic signature. In this work, we investigate the topological relations between landslides and archaeological sites for nine selected settlements in the Moldavian Plateau, situated on ridges and hillslopes. Landslides and sites were mapped using high resolution LiDAR DEMs and extensive field validation activities. Landslides were classified as very old (relict), old, and recent, according to their morphologic appearance. We argue the possibility of (i) assigning a relative age to the three main classes of landslides as they appear on the present day topography, and (ii) assessing the landslide activity during the Holocene. Using this information, we set up a model of landslide evolution during the Holocene for the lowland of Eastern Carpathians. Based on collected data, we cannot exclude the Pleistocene age for some very old landslides, whereas the old and recent landslides appeared during the Holocene. We think this approach can be extended to other archaeological sites of the study area, and to other areas. Furthermore, similar studies can prove useful for landslide hazard analyses, helping to adopt adequate protection and mitigation measures, framed in a climate change scenario.